X-ray and NMR Crystallography Studies of Novel Theophylline Cocrystals Prepared by Liquid Assisted Grinding - Fernandes, Jose A.
Two new cocrystals of, theophylline were pared by liquid assisted grinding. While compound 1 (theophylline:4-aminosalicylic acid 2:1) was characterized by single crystal X-ray diffraction, the crystal structure of compound 2 (theophylline:4-aminobenzoic acid 1:1) was determined by combining. X-ray: powder diffraction (XRPD), solid-state NMR and DFT calculations. The use of 1D/2D H-1 high resolution solid-state NMR techniques provided structural insight on local length scales revealing internuclear proximities and relative orientations between the building blocks of compound 2, thus providing information on the type of hydrogen bond synthons, formed. DFT - calculations were also employed to generate meaningful structures and calculate NMR H-1 and C-13 chemical shifts to further validate the XRPD model. Compound 2 shows an unusual structure, in which the amino groups do not participate in hydrogen bonds, While compound exhibits an extended hydrogen-bonding network, in which planar subunits can be recognized.